Start Your Own Freelance Writing Business - The Staff of Entrepreneur Media, Inc; Briggs, Laura (Ascent Audio, 2019)
Breaking into freelance writing has gotten much easier for word-savvy entrepreneurs like you. But even in the golden age of content creation, you still need to know what it takes to launch and consistently pitch your services so you can grow and scale your freelance writing side hustle into a full-fledged career you really love. Start Your Own Freelance Writing Business is an easy-to-understand, introductory, and nontechnical approach to the world of freelance writing. This book teaches you how to leverage the fast-changing pace of technology to grow a business that gives you the freedom and flexibility you want. You'll learn how to assess your freelancing skillset; determine the best way to position your business to clients; research the most profitable freelance writing opportunities; create a series of pitches that convert to profitable client relationships; use freelance job sites to build a strong client base; master the art of time management so you don't miss a single deadline; and market your business in multiple channels to grow and scale your business. You'll also get an inside look at a freelance writing business and related tips and strategies from a multi-six figure online freelance writer. So what are you waiting for? The time is "write" to start today!